2013
DOI: 10.1155/2013/765253
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Aortic Stiffness Is Increased in Systemic Lupus Erythematosus Activity in Children and Adolescents

Abstract: Patients with systemic lupus erythematosus (SLE) are prone to premature atherosclerosis and are at risk for the development of cardiovascular disease. Increased arterial stiffness is emerging as a marker of subclinical atherosclerosis. Purpose. To measure proximal aortic stiffness in children and adolescents with SLE. Methods. We studied 16 patients with SLE in activity (mean age 15 ± 2.42 years; 16 females), 14 patients with SLE not in activity (mean age 15.7 ± 1.89 years; 4 males, 10 females), and 16 age- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Ongoing inflammation may have an effect on the increased aortic stiffness etiology in patients with CD. El Gamal et al 24) investigated patients with systemic lupus erythematous, an autoimmune disorder like CD, and asserted that increased aortic stiffness was associated with disease activity and inflammation rather than the atherosclerotic process. In another study, Barbulescu et al 25) found that increased aortic stiffness was associated with levels of the inflammatory markers: C-reactive protein and interleukin-6.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing inflammation may have an effect on the increased aortic stiffness etiology in patients with CD. El Gamal et al 24) investigated patients with systemic lupus erythematous, an autoimmune disorder like CD, and asserted that increased aortic stiffness was associated with disease activity and inflammation rather than the atherosclerotic process. In another study, Barbulescu et al 25) found that increased aortic stiffness was associated with levels of the inflammatory markers: C-reactive protein and interleukin-6.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ghosh et al observed increased fibromuscular dysplasia (FMD) and cIMT in 60 Indian patients with SLE who showed impaired FMD and abnormal IMT [48]. Our group has a greater proportion of African American patients than other paediatric studies [22][23][24][25][26][27], and this may have affected the results.…”
Section: Discussionmentioning
confidence: 71%
“…Although these authors showed an increased burden of traditional and non-traditional CV risk factors among the cohort, such as HTN, these did not correlate with changes in vascular measures. When subdivided by disease activity, El Gamal et al [26] showed increased PWV in hypertensive patients with active SLE when compared to controls, but no difference between controls and patients with inactive disease as defined by SLEDAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by El Gramal, et al [ 69 ], 16 adolescent patients with active SLE (mean age 15 ± 2.42 years; 16 females), 14 patients with inactive SLE (mean age 15.7 ± 1.89 years; 4 males, 10 females), and 16 age and sex-matched healthy adolescents (15.5 ± 1.71 years; 4 males, 12 females) underwent echocardiography for assessment of proximal aortic PWV [defined as Ao distance/Ao wave transit time in the aortic arch]. Patients with active SLE had significantly higher PWV values than controls (p<0.05), while no difference was found between patients with inactive SLE and controls.…”
Section: Diagnostic Methodsmentioning
confidence: 99%